That was then but this is now: multifunctionality in industry and agriculture - Díaz-Bonilla, Eugenio; Tin, Jonathan (International Food Policy Research Institute, 2002)
Current agricultural negotiations in the World Trade Organization are grappling on how to fully integrate agriculture within the general rules for trade in goods. The notion of multifunctionality of agriculture has been suggested as a reason to justify special treatment for that sector, including the continuation of its protection and subsidization. Many developing countries are still analyzing whether the idea has something to offer them in terms of their negotiating positions and policy framework. While multifunctionality has been invoked for supporting agriculture in developed countries, a similar idea, although not called so at the time, was clearly behind support for industry in developing countries. Again in this case, the policy implication was that government intervention was required (through trade protection, subsidies, and other special policies) to develop an industrial base that contributed to society more than what market valuations alone would suggest. The debate on industrialization in developing countries was part of a broader discussion regarding nation-building, economic development, and social modernization. The current arguments around multifunctionality are similarly embedded in a larger economic, political and social matrix. This paper, although it does not present a full account of either debate, discusses some of the intriguing parallelisms in their theoretical frameworks, policy implications and economic and social impacts. The main objective is to clarify current policy issues for the agricultural sector in developing countries, highlighting possible consequences for the negotiating position of developing countries in the WTO process.